1989
DOI: 10.1073/pnas.86.11.4071
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of regulatory domains of early (beta) and late (gamma 2) genes by construction of chimeric genes expressed in herpes simplex virus 1 genomes.

Abstract: The (14). An additional site mapping downstream from the nucleotide +51 was also found (unpublished work).The significant features of Y2 gene regulation are that (i) expression initiates after the onset of DNA synthesis and continues late in infection; (ii) the requirement for viral DNA synthesis is cis-acting; (iii) 72 genes residing permanently or transiently in cells are induced by infection of the cells, but they are regulated as 83 rather than 72 genes; and (iv) it has been reported that the sequences re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 32 publications
2
36
0
Order By: Relevance
“…Fifth, the ICP8 recombinase activity could lead to conformational changes in viral progeny DNA that allow efficient late gene transcription. cis-acting changes in viral genomes following viral DNA replication are known to activate late gene transcription (26). ICP8 is known to bind to viral progeny DNA (23), and the recombinase activity of ICP8 could act to resolve concatemers and increase viral late gene transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, the ICP8 recombinase activity could lead to conformational changes in viral progeny DNA that allow efficient late gene transcription. cis-acting changes in viral genomes following viral DNA replication are known to activate late gene transcription (26). ICP8 is known to bind to viral progeny DNA (23), and the recombinase activity of ICP8 could act to resolve concatemers and increase viral late gene transcription.…”
Section: Discussionmentioning
confidence: 99%
“…While early viral gene promoters typically consists of distal regulatory sequences upstream of the TATA box, the critical elements of late promoters have been mapped to regions near the transcription start sites (8,10,12,13,16,25,32,36). These cis-acting elements include a TATA box (8,12,16), an initiator element at the transcription start site (32,36), and a downstream activation sequence in the 5Ј-untranslated region (10,13,25). Multiple HSV proteins (ICP4, ICP8, and ICP27) have been shown to be necessary for efficient expression of late genes (9,20,28).…”
mentioning
confidence: 99%
“…We are faced, however with enormous gaps. Although promoter substitutions revealed that the sequences conferring γ 2 specificity resides in the 5’ transcribed noncoding domain downstream of the TATA box (Mavromara et al, 1989), we have no cohesive pictures for the differential expression of β and γ 2 genes.…”
Section: Productive Infection At the Portal Of Entrymentioning
confidence: 78%